Early Lateral Closing Wedge Surgical Correction of Cubitus Varus Deformity Complicating Supracondylar Humeral Fracture in Children - Dr. Yousif Awad Jaber Almarawee (Zien Journals, 2024)
Cubitus varus deformity complicating supracondylar fracture of humerus in children usually implies a malunion from inappropriate treatment of the fracture . The resulting deformity can be solved only by osteotomy ,since the deformity once established it will not correct by remodeling . A lot of controversy is still present regarding the best age of the child to perform the corrective osteotomy . Cosmetic appearance is the most common indication for osteotomy
Keywords: common; appearance; complicating; osteotomy